CNCs-coated MoS2 / PVDF composite piezoelectric material, and preparation method and application of piezoelectric nano-generator
By preparing CNCs@MoS2/PVDF composite piezoelectric material, wet spinning and subsequent processing technology, the problem of poor performance of existing piezoelectric nanomaterials was solved, and the mechanical properties and piezoelectric properties of the material were significantly improved.
Patent Information
- Application Number
- CN202411305239.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-03-11
AI Technical Summary
The existing piezoelectric nanomaterials prepared based on electrospinning have problems with poor piezoelectric properties and mechanical properties, which limits their practical application.
CNCs@MoS2/PVDF composite material was used to mix cellulose nanocrystals with molybdenum disulfide to prepare CNCs@MoS2 composite material, and dissolve it with PVDF in an organic solvent, and prepare primary fibers by wet spinning, followed by thermal drafting, thermal setting, twisting, braiding and high-pressure polarization to obtain CNCs@MoS2/PVDF composite piezoelectric material.
The mechanical properties and thermal stability of CNCs@MoS2/PVDF composite piezoelectric materials are significantly improved, making the PVDF dipoles fully oriented, imparting excellent piezoelectric properties to the material, and improving the appearance quality of the fibers.
Smart Images

Figure CN119604179A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of piezoelectric energy conversion technology, and in particular to a CNCs@MoS 2 Preparation methods and applications of / PVDF composite piezoelectric materials and piezoelectric nanogenerators. Background Art
[0002] Piezoelectric nanogenerators (PENGs) can convert mechanical energy into electrical energy and have attracted great attention as an alternative solution to the energy problem of future small electronic devices. In particular, piezoelectric nanogenerators based on polyvinylidene fluoride (PVDF) have multifunctional properties such as high sensitivity, flexibility, stretchability, and multi-shape variability, and can be used for stable and continuous operation of self-powered sensors. However, PVDF piezoelectric nanomaterials prepared by electrospinning have defects such as small piezoelectric coefficient, low output signal, and low mechanical properties, which greatly limit their practical applications. Therefore, it is necessary to develop piezoelectric materials with excellent piezoelectric and physical properties to improve the performance of piezoelectric nanogenerators. Summary of the invention
[0003] This application discloses a CNCs@MoS 2 The preparation method and application of / PVDF composite piezoelectric materials and piezoelectric nanogenerators are aimed at solving the technical problems of poor piezoelectric and mechanical properties of existing piezoelectric nanomaterials prepared based on electrospinning.
[0004] In order to achieve the above purpose, the technical solution of this application is:
[0005] The first aspect of the present application provides a CNCs@MoS 2 A method for preparing a / PVDF composite piezoelectric material, the method comprising:
[0006] Cellulose nanocrystals were mixed with molybdenum disulfide to prepare CNCs@MoS 2 Composite materials;
[0007] The CNCs@MoS 2 The composite material and PVDF were dissolved in an organic solvent to obtain CNCs@MoS 2 / PVDF composite solution;
[0008] The CNCs@MoS 2 The CNCs@MoS@C ... 2 / PVDF fiber;
[0009] The CNCs@MoS 2The CNCs@MoS / PVDF fibers are twisted, woven and polarized under high voltage to obtain the CNCs@MoS 2 / PVDF composite piezoelectric material.
[0010] In combination with the first aspect, preferably, the mass ratio of the cellulose nanocrystals to molybdenum disulfide is 1:(1-3).
[0011] In combination with the first aspect, preferably, the molecular weight of the PVDF is 400,000-700,000;
[0012] And / or, the mass percentage of the PVDF in the composite solution is 30%-40%;
[0013] And / or, the organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
[0014] In combination with the first aspect, preferably, the preparation of the spun fiber by wet spinning comprises sequentially performing a coagulation bath, a primary drawing bath, a secondary drawing bath, a washing bath, heat drying and winding;
[0015] And / or, the coagulation bath is a 5%-40% aqueous solution of N,N-dimethylformamide at a temperature of 30-70°C;
[0016] and / or, the primary drawing bath and the secondary drawing bath are both aqueous solutions at a temperature of 60-90° C.;
[0017] And / or, the draft ratio of the primary drafting bath is 1-4;
[0018] and / or, the draft ratio of the secondary drafting bath is 1-3;
[0019] and / or, the washing bath is a methanol solution at a temperature of 20-30°C;
[0020] And / or, the thermal drying temperature is 100-150°C.
[0021] In combination with the first aspect, preferably, when the spun fiber is subjected to heat drawing and heat setting in sequence, the temperature of the heat drawing is 80-140° C., and the drawing ratio is 2-5;
[0022] And / or, the heat setting temperature is 100-150°C.
[0023] In combination with the first aspect, preferably, the high voltage polarization includes corona polarization;
[0024] The corona polarization temperature is 80-120° C., the voltage is 10-20 kV, and the time is 2-4 hours.
[0025] The second aspect of the present application provides a CNCs@MoS2 / PVDF piezoelectric nanogenerator, comprising a piezoelectric material layer, a conductive layer, a packaging layer and a wire, wherein the raw material for preparing the piezoelectric material layer comprises the CNCs@MoS prepared by the preparation method described in the first aspect 2 / PVDF composite piezoelectric material.
[0026] The third aspect of the present application provides the CNCs@MoS 2 / A method for preparing a PVDF piezoelectric nanogenerator, the method comprising:
[0027] The CNCs@MoS 2 After the / PVDF composite piezoelectric material is prepared into a piezoelectric material layer, a conductive layer and a packaging layer are sequentially arranged on the upper surface of the piezoelectric material layer, and a conductive layer and a packaging layer are sequentially arranged on the lower surface of the piezoelectric material layer, and a wire is used to electrically connect the two conductive layers to obtain the CNCs@MoS 2 / PVDF piezoelectric nanogenerator.
[0028] In combination with the third aspect, preferably, the conductive layer includes one or more of aluminum, gold, titanium, titanium nitride, titanium silicide, titanium tungsten alloy, tungsten, tungsten silicide, tungsten nitride, nickel, nickel silicide, nickel nitride, tantalum, tantalum nitride, iron, platinum, copper, silver and chromium;
[0029] And / or, the encapsulation layer includes one or more of a polyimide film, a polyethylene film, a polytetrafluoroethylene film, a polypropylene film, a polystyrene film, and a benzocyclobutene film.
[0030] The fourth aspect of the present application provides CNCs@MoS prepared by the preparation method of the third aspect. 2 / Application of PVDF piezoelectric nanogenerators in human motion monitoring and energy harvesting.
[0031] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:
[0032] The preparation method provided in this application prepares CNCs@MoS by wet spinning technology 2 / PVDF nascent fibers, and the nascent fibers are subjected to a combination of post-treatments of heat drawing, heat setting, twisting, weaving and high-voltage polarization in sequence, among which, on the one hand, the CNCs@MoS 2 / PVDF fiber orientation and crystallinity make CNCs@MoS 2 / PVDF composite piezoelectric material has good mechanical properties and thermal stability, and can fully orient the PVDF dipoles, giving CNCs@MoS 2 / PVDF composite piezoelectric material has excellent piezoelectric properties; on the other hand, it can make the prepared CNCs@MoS 2 / PVDF fibers are not easy to adhere and have uniform structure, which effectively improves the appearance quality of the fibers; thirdly, CNCs can be filled in MoS through hydrogen bonding. 2 The interlayer, as well as the synergistic effect between CNCs and PVDF through ion dipole-hydrogen bonds promote the formation of piezoelectric phase. The synergistic effect among the three makes the CNCs@MoS2 / PVDF composite piezoelectric material have excellent piezoelectric and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 A process flow chart for preparing spun fibers provided in an embodiment of the present application;
[0035] Figure 2 CNCs@MoS provided in the embodiment of the present application 2 / PVDF fiber post-drawing process flow chart;
[0036] Figure 3 The CNCs and MoS provided in the embodiments of the present application 2 and CNCs@MoS 2 X-ray diffraction pattern of
[0037] Figure 4 The α1-spun fibers, β1-PVDF fibers and α1-CNCs@MoS provided in the embodiments of the present application are 2 / Stress-strain curve of PVDF fiber;
[0038] Figure 5 α1-CNCs@MoS provided in the embodiment of the present application 2 Variable temperature infrared spectra of / PVDF fiber and β1-PVDF fiber;
[0039] Figure 6 The α1-spun fibers, β1-PVDF fibers and α1-CNCs@MoS provided in the embodiments of the present application are 2 / X-ray diffraction pattern of PVDF fiber;
[0040] Figure 7 α1-CNCs@MoS provided in the embodiment of the present application 2 / PVDF composite piezoelectric materials, β1-PVDF piezoelectric materials and β2-CNCs@MoS 2 Piezoelectric constant test results of / PVDF composite piezoelectric materials;
[0041] Figure 8 The β1-PVDF piezoelectric nanogenerator and β3-MoS 2 / PVDF piezoelectric nanogenerator, β2-CNCs@MoS 2 / PVDF and α1-CNCs@MoS 2 / The voltage diagram generated by the PVDF piezoelectric nanogenerator under a periodic pressure of 5 kPa;
[0042] Fig. 9 ɑ1-CNCs@MoS provided in the embodiment of the present application 2 / Image of PVDF piezoelectric nanogenerator monitoring human movement. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0044] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0045] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0046] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0047] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0048] It should be noted that all raw materials and reagents in the examples of the present application are purchased on the market or prepared according to conventional methods well known to those skilled in the art. For example, PVDF, N,N-dimethylformamide, methanol, aluminum, gold, titanium, titanium nitride, titanium silicide, polyimide film, polyethylene film, polytetrafluoroethylene film, polypropylene film, etc. are all purchased on the market.
[0049] In the first aspect, the present application embodiment provides a CNCs@MoS 2 A method for preparing a / PVDF composite piezoelectric material, the method comprising:
[0050] Cellulose nanocrystals were mixed with molybdenum disulfide to prepare CNCs@MoS 2 Composite materials;
[0051] The CNCs@MoS 2 The composite material and PVDF were dissolved in an organic solvent to obtain CNCs@MoS 2 / PVDF composite solution;
[0052] The CNCs@MoS 2 The CNCs@MoS@C ... 2 / PVDF fiber;
[0053] The CNCs@MoS 2 The CNCs@MoS / PVDF fibers are twisted, woven and polarized under high voltage to obtain the CNCs@MoS 2 / PVDF composite piezoelectric material.
[0054] Among them, on the one hand, it can greatly increase and effectively fix the formed CNCs@MoS 2 / PVDF fiber orientation and crystallinity make CNCs@MoS 2 / PVDF composite piezoelectric material has good mechanical properties and thermal stability, and can fully orient the PVDF dipoles, giving CNCs@MoS 2 / PVDF composite piezoelectric material has excellent piezoelectric properties; on the other hand, it can make the prepared CNCs@MoS 2 / PVDF fibers are not easy to adhere and have uniform structure, which effectively improves the appearance quality of the fibers; thirdly, CNCs can be filled in MoS through hydrogen bonding. 2 The interlayer, as well as the synergistic effect between CNCs and PVDF through ion dipole-hydrogen bonds promote the formation of piezoelectric phase. The synergistic effect among the three makes the CNCs@MoS2 / PVDF composite piezoelectric material have excellent piezoelectric and mechanical properties.
[0055] It should be noted that polyvinylidene fluoride, referred to as PVDF, is a high-performance synthetic polymer material with alternating CH 2 and CF 2 The groups give PVDF unique polarity and affect the solubility and piezoelectric properties of the material. In the chemical structure, CF is bonded by chemical bonds. This short-bond structure forms a stable and firm bond with hydrogen ions, thus having specific physical and chemical properties. It not only has strong wear resistance and impact resistance, but also has high anti-fading and anti-ultraviolet properties in extremely harsh and adverse environments.
[0056] It should be noted that molybdenum disulfide (MoS 2 ) as a layered transition metal sulfide has become a hot topic in nanoscience research due to its special properties in electronic, optical and mechanical properties. The preparation of a single layer or a few layers is crucial to achieve these properties. Cellulose nanocrystals (CNCs), as a bio-based and renewable nanomaterial, have become an ideal dispersant due to their unique chemical stability, high specific surface area and good mechanical properties. Through the introduction of CNCs, not only can MoS 2 The effective peeling can significantly reduce the number of molybdenum disulfide layers after peeling, and can also improve the thermal stability and mechanical strength of the obtained material.
[0057] In the embodiment of the present application, the CNCs and MoS 2 The mass ratio of CNCs and MoS is preferably 1:(1-3), such as 1:1, 1:2, 1:3 or any ratio within this range. 2 The mass ratio of MoS 2 Exfoliation into 2H-MoS 2 Nanosheets, making the prepared CNCs@MoS 2 The composite material has excellent electrical properties and stability. At the same time, CNCs are sandwiched between MoS2 2H-MoS is added to the nanosheets 2 The layer spacing.
[0058] In the embodiment of the present application, the molecular weight of the PVDF is preferably 400,000-700,000; the mass percentage of PVDF in the composite solution is preferably 30%-40%; the organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide. 2 The composite material and PVDF were dissolved in an organic solvent to obtain uniform and stable CNCs@MoS 2 / PVDF composite solution, before spinning, is subjected to pre-spinning preparation steps such as mixing, filtering and degassing to make CNCs@MoS 2 The properties of the / PVDF composite solution are uniform and consistent, and the gel blocks and impurities entrained in the solution are removed and the bubbles in the liquid are removed.
[0059] In an embodiment of the present application, the preparation of primary fibers by wet spinning includes a coagulation bath, a primary drawing bath, a secondary drawing bath, a washing bath, heat drying and winding in sequence; the coagulation bath is preferably an aqueous solution of 5%-40% N,N-dimethylformamide, and the temperature is preferably 30-70°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C or any temperature within the range; the primary drawing bath and the secondary drawing bath are both aqueous solutions, and the temperature is preferably 60-90°C, for example, 60°C, 70°C, 80°C, 90°C or any temperature within the range ; The drafting ratio of the first drafting bath is preferably 1-4, for example, 1, 2, 3, 4 or any value within this range; The drafting ratio of the second drafting bath is preferably 1-3, for example, 1, 2, 3 or any value within this range; The washing bath is preferably a methanol solution, and the temperature is preferably 20-30°C, for example, 20°C, 25°C, 30°C or any temperature within this range; The temperature of the thermal drying is preferably 100-150°C, for example, 100°C, 110°C, 120°C, 130°C, 150°C or any temperature within this range. Among them, by controlling the process parameters during the drafting process, the orientation degree of the PVDF fiber structure is greatly increased, the porosity is reduced, and the internal orientation structure of the fiber can be further improved after two differential draftings, while the mechanical properties of the fiber are improved.
[0060] In the embodiment of the present application, when the spun fibers are subjected to heat drawing and heat setting in sequence, the temperature of the heat drawing is preferably 80-140°C, such as 80°C, 100°C, 120°C, 140°C or any temperature within the range, and the drawing ratio is preferably 2-5, such as 2, 3, 4, 5 or any value within the range; the heat setting temperature is preferably 100-150°C, such as 100°C, 120°C, 130°C, 150°C or any temperature within the range. Among them, the process of stretching and orienting the spun fibers is the process of oriented crystallization rearrangement of the fiber molecular structure, which reduces the fiber diameter under the action of external force, deforms the fiber in the direction of the force, and the flexible molecular chains in the fiber stretch, deform, rearrange and orient unidirectionally in the direction of the force, and simultaneously produces crystallization. As the macromolecules in the fiber are oriented along the fiber axis, hydrogen bonds, dipole bonds and other types of intermolecular forces are formed and increased, the number of molecular chains that the fiber bears the applied tension increases, the distance between molecules decreases, and the structure becomes compact, thereby significantly improving the fiber's breaking strength, reducing elongation, and significantly improving wear resistance and fatigue strength to various types of deformation. The heat setting process uses heat to eliminate the internal stress generated by the fabric fiber during the stretching process, allowing the macromolecules to relax to a certain extent, fixing the shape of the woven fiber and fixing the orientation of the fiber.
[0061] In the embodiment of the present application, the high-voltage polarization includes corona polarization; the temperature of the corona polarization is 80-120°C, for example, 80°C, 100°C, 110°C, 120°C or any temperature in the range, the polarization voltage is preferably 10-20kV, for example, 10kV, 15kV, 20kV or any voltage in the range, and the polarization time is preferably 2-4h, for example, 2h, 3h, 4h or any time in the range. Among them, the high-voltage polarization uses the corona polarization method to fully orient the PVDF dipoles, thereby giving CNCs@MoS 2 / PVDF composite piezoelectric material has excellent piezoelectric properties.
[0062] In a second aspect, the present application embodiment provides a CNCs@MoS 2 / PVDF piezoelectric nanogenerator, comprising a piezoelectric material layer, a conductive layer, a packaging layer and a wire, wherein the raw material for preparing the piezoelectric material layer comprises the CNCs@MoS prepared by the preparation method described in the first aspect 2 / PVDF composite piezoelectric material.
[0063] In a third aspect, the present application embodiment provides a CNCs@MoS 2 / A method for preparing a PVDF piezoelectric nanogenerator, the method comprising:
[0064] The CNCs@MoS 2After the / PVDF composite piezoelectric material is prepared into a piezoelectric material layer, a conductive layer and a packaging layer are sequentially arranged on the upper surface of the piezoelectric material layer, and a conductive layer and a packaging layer are sequentially arranged on the lower surface of the piezoelectric material layer, and a wire is used to electrically connect the two conductive layers to obtain the CNCs@MoS 2 / PVDF piezoelectric nanogenerator.
[0065] It should be noted that the CNCs@MoS prepared in this application 2 / PVDF piezoelectric nanogenerators exhibit excellent electrical properties, specifically the piezoelectric coefficient d 33 Reaching 42pC / N, power density is 60.6μW / cm 2 .
[0066] In the embodiment of the present application, the conductive layer is preferably one or more of aluminum, gold, titanium, titanium nitride, titanium silicide, titanium tungsten alloy, tungsten, tungsten silicide, tungsten nitride, nickel, nickel silicide, nickel nitride, tantalum, tantalum nitride, iron, platinum, copper, silver and chromium; the encapsulation layer is preferably one or more of polyimide film, polyethylene film, polytetrafluoroethylene film, polypropylene film, polystyrene film, benzocyclobutene film. Among them, the material selected for the conductive layer is CNCs@MoS 2 The main function of the piezoelectric nanogenerator in CNCs@MoS is to transmit signals and conduct current on the circuit board. 2 / The main function of PVDF piezoelectric nanogenerator is to protect the internal structure of the piezoelectric nanogenerator from the influence of the external environment, and to prevent the electronic components inside the piezoelectric nanogenerator from being corroded and damaged by moisture, dust, chemicals, etc.
[0067] In a fourth aspect, the present application also provides the CNCs@MoS 2 / PVDF piezoelectric nanogenerators in human motion monitoring and energy harvesting. 2 / PVDF piezoelectric nanogenerator has the advantages of excellent mechanical properties, excellent piezoelectric properties and stability. 2 / PVDF piezoelectric nanogenerator has excellent piezoelectric output performance when used in human motion monitoring and energy harvesting.
[0068] The technical solution of the present application will be further described below in conjunction with the embodiments of the present application.
[0069] Example 1
[0070] The α1-CNCs@MoS provided in the embodiment of the present application 2The preparation method of / PVDF composite piezoelectric material comprises the following steps:
[0071] S101-Preparation of CNCs@MoS 2 Composite Materials
[0072] Weigh 1.5 g of dried CNCs and 1.5 g of MoS 2 After grinding and mixing, the powder was added to 100 g of deionized water and stirred at room temperature to mix the powder evenly in the water. The powder was then ultrasonically treated. The upper suspension after centrifugation was transferred to an evaporating dish and freeze-dried to obtain CNCs@MoS 2 Composite materials;
[0073] S102-Preparation of CNCs@MoS 2 / PVDF composite solution
[0074] Weigh 2 g CNCs@MoS 2 The composite material and 30.6 g PVDF were added into 70 g DMF and mechanically stirred at 70 °C for 2 h to obtain CNCs@MoS with a mass fraction of 31%. 2 / PVDF composite solution;
[0075] S103-Wet spinning to prepare nascent fibers, according to Figure 1 The process shown includes:
[0076] The obtained CNCs@MoS 2 The / PVDF composite solution was degassed under a pressure of 0.7MPa, and then the solution was wet-spun according to the process of coagulation bath, primary drawing bath (drawing temperature 60℃, drawing ratio 2), secondary drawing bath (drawing temperature 60℃, drawing ratio 2), washing bath (temperature 20℃), heat drying (temperature 120℃), and winding to obtain α1-spun fibers. The specifications of the spinneret are 50 holes × 0.2mm, and the spinning pressure is 0.3MPa;
[0077] S104- Heat drawing and heat setting of nascent fibers, according to Figure 2 The process shown includes:
[0078] The obtained α1-spun fibers were subjected to post-stretching (stretching ratio of 2) through a hot stretching and heat setting process to obtain α1-CNCs@MoS 2 / PVDF fiber; wherein the heat drawing temperature is 80°C and the heat setting temperature is 100°C;
[0079] S105-Preparation of α1-CNCs@MoS 2 / PVDF composite piezoelectric material
[0080] The obtained α1-CNCs@MoS 2 / PVDF fibers were twisted and woven into CNCs@MoS 2 / PVDF fabric and CNCs@MoS 2 The α1-CNCs@MoS / PVDF fabric was subjected to high voltage polarization under the following conditions: polarization temperature 80 °C, polarization voltage 10 kV, and polarization time 2 h. 2 / PVDF composite piezoelectric material.
[0081] Example 2
[0082] The present application embodiment provides α1-CNCs@MoS 2 / The preparation method of PVDF piezoelectric nanogenerator specifically comprises:
[0083] The obtained α1-CNCs@MoS 2 / PVDF composite piezoelectric material, set on α1-CNCs@MoS 2 The conductive layer copper on the upper surface and the lower surface of the / PVDF composite piezoelectric material, the encapsulation layer polyimide film respectively covered on the conductive layer and the wires respectively connected to the conductive layer are composited to obtain the α1-CNCs@MoS 2 / PVDF piezoelectric nanogenerator.
[0084] Example 3
[0085] Preparation of α2-CNCs@MoS in this application example 2 The preparation method of / PVDF composite piezoelectric material specifically comprises:
[0086] S201: Weigh 1.5 g of dried CNCs and 3.0 g of MoS 2 After grinding and mixing, the powder was added to 100 g of deionized water and stirred at room temperature to mix the powder evenly in the water. The powder was then ultrasonically treated. The upper suspension after centrifugation was transferred to an evaporating dish and freeze-dried to obtain CNCs@MoS 2 Composite materials;
[0087] S202: Weigh 2 g CNCs@MoS 2 The composite material and 35.7 g PVDF were added into 70 g DMF and mechanically stirred at 70 °C for 2 h to obtain CNCs@MoS with a mass fraction of 37%. 2 / PVDF composite solution;
[0088] S203: The obtained CNCs@MoS 2The / PVDF composite solution was degassed under a pressure of 0.7MPa, and then the solution was wet-spun according to the process of coagulation bath, primary drawing bath (drawing temperature 60℃, drawing ratio 2), secondary drawing bath (drawing temperature 60℃, drawing ratio 2), washing bath (temperature 20℃), heat drying (temperature 120℃), and winding to obtain α2-spun fibers. The specifications of the spinneret are 50 holes × 0.2mm, and the spinning pressure is 0.3MPa;
[0089] S204: The obtained α2-spun fiber is subjected to post-stretching (stretching ratio is 3) through a process of heat stretching and heat setting to obtain α2-CNCs@MoS 2 / PVDF fiber; wherein the heat drawing temperature is 80°C and the heat setting temperature is 100°C;
[0090] S205: The obtained α2-CNCs@MoS 2 The α2-CNCs@MoS / PVDF fibers were twisted and woven into 2 / PVDF fabric and α2-CNCs@MoS 2 The α2-CNCs@MoS / PVDF fabric was subjected to high voltage polarization under the following conditions: polarization temperature 80 °C, polarization voltage 10 kV, and polarization time 2 h. 2 / PVDF composite piezoelectric material.
[0091] Example 4
[0092] The present application embodiment provides α2-CNCs@MoS 2 / The preparation method of PVDF piezoelectric nanogenerator specifically comprises:
[0093] The obtained α2-CNCs@MoS 2 / PVDF composite piezoelectric material, set on α2-CNCs@MoS 2 The conductive layer copper on the upper and lower surfaces of the / PVDF composite piezoelectric material, the encapsulation layer polyimide covering the conductive layer, and the wires connected to the conductive layer are compounded to obtain α2-CNCs@MoS 2 / PVDF piezoelectric nanogenerator.
[0094] Example 5
[0095] The α3-CNCs@MoS 2 The distribution ratio, preparation operation and process parameters of the piezoelectric nanogenerator group are basically the same as those in Example 1. The difference is that the α3-CNCs@MoS 2The α3-CNCs@MoS / PVDF fiber was post-stretched (stretching ratio was 4) through the process of hot stretching and heat setting to obtain α3-CNCs@MoS 2 / PVDF fiber, assembled to obtain α3-CNCs@MoS 2 / PVDF piezoelectric nanogenerator.
[0096] Example 6
[0097] The α4-CNCs@MoS 2 The distribution ratio, preparation operation and process parameters of the piezoelectric nanogenerator group are basically the same as those in Example 1. The difference is that the α4-CNCs@MoS 2 The α4-CNCs@MoS / PVDF fiber was post-stretched (stretching ratio was 5) through the process of heat drawing and heat setting to obtain α4-CNCs@MoS 2 / PVDF fiber, assembled to obtain α4-CNCs@MoS 2 / PVDF piezoelectric nanogenerator.
[0098] Example 7
[0099] Preparation of α5-CNCs@MoS in the present application 2 The preparation method of / PVDF composite piezoelectric material specifically comprises:
[0100] S501: Weigh 1.5 g of dried CNCs and 4.5 g of MoS 2 After grinding and mixing, the powder was added to 100 g of deionized water and stirred at room temperature to mix the powder evenly in the water. The powder was then ultrasonically treated. The upper suspension after centrifugation was transferred to an evaporating dish and freeze-dried to obtain CNCs@MoS 2 Composite materials;
[0101] S502: Weigh 2 g CNCs@MoS 2 The composite material and 40.8 g PVDF were added into 60 g DMF and mechanically stirred at 70 °C for 2 h to obtain α5-CNCs@MoS with a mass fraction of 42%. 2 / PVDF composite solution;
[0102] S503: The obtained α5-CNCs@MoS 2The / PVDF composite solution was degassed under a pressure of 0.7MPa, and then the solution was wet-spun according to the process of coagulation bath, primary drawing bath (drawing temperature 90℃, drawing ratio 4), secondary drawing bath (drawing temperature 70℃, drawing ratio 3), washing bath (temperature 30℃), heat drying (temperature 150℃), and winding to obtain α5-spun fibers. The specifications of the spinneret are 50 holes × 0.2mm, and the spinning pressure is 0.3MPa;
[0103] S504: The obtained raw fiber is subjected to a post-drawing process (drawing ratio is 3) through a hot drawing and heat setting process to obtain α5-CNCs@MoS 2 / PVDF fiber; wherein the heat drawing temperature is 140°C and the heat setting temperature is 150°C;
[0104] S505: The obtained α5-CNCs@MoS 2 The / PVDF fibers were twisted and woven into fabrics, and the α5-CNCs@MoS 2 The α5-CNCs@MoS / PVDF fabric was subjected to high voltage polarization under the following conditions: polarization temperature 120 °C, polarization voltage 20 kV, and polarization time 3 h. 2 / PVDF composite piezoelectric material.
[0105] Example 8
[0106] The present application embodiment provides α5-CNCs@MoS 2 / The preparation method of PVDF piezoelectric nanogenerator specifically comprises:
[0107] The obtained α5-CNCs@MoS 2 / PVDF composite piezoelectric material, set on α5-CNCs@MoS 2 The conductive layers of silver on the upper and lower surfaces of the / PVDF composite piezoelectric material, the encapsulation layers of polyethylene films respectively covering the conductive layers, and the wires respectively connected to the conductive layers are composited to obtain α5-CNCs@MoS 2 / PVDF piezoelectric nanogenerator.
[0108] Example 9
[0109] The present application embodiment provides α6-CNCs@MoS 2 The preparation method of / PVDF composite piezoelectric material specifically comprises:
[0110] S601: Weigh 1.5 g of dried CNCs and 4.5 g of MoS 2After grinding and mixing, the powder was added to 100 g of deionized water and stirred at room temperature to mix the powder evenly in the water. The powder was then ultrasonically treated. The upper suspension after centrifugation was transferred to an evaporating dish and freeze-dried to obtain CNCs@MoS 2 Composite materials;
[0111] S602: Weigh 2 g CNCs@MoS 2 The composite material and 35.7 g PVDF were added into 80 g DMF and mechanically stirred at 70 °C for 2 h to obtain α6-CNCs@MoS with a mass fraction of 37%. 2 / PVDF composite solution;
[0112] S603: The obtained α6-CNCs@MoS 2 The / PVDF composite solution was degassed under a pressure of 0.7MPa, and then the solution was wet-spun according to the process of coagulation bath, primary drawing bath (drawing temperature 80℃, drawing ratio 3), secondary drawing bath (drawing temperature 80℃, drawing ratio 2), washing bath (temperature 25℃), heat drying (temperature 100℃), and winding to obtain α6-spun fibers. The specifications of the spinneret are 50 holes × 0.2mm, and the spinning pressure is 0.3MPa;
[0113] S604: The obtained raw fiber is subjected to a post-drawing process (drawing ratio is 4) through a hot drawing and heat setting process to obtain α6-CNCs@MoS 2 / PVDF fiber; wherein the heat drawing temperature is 100°C and the heat setting temperature is 130°C;
[0114] S605: The obtained α6-CNCs@MoS 2 The / PVDF fibers were twisted and woven into fabrics, and the α6-CNCs@MoS 2 The α6-CNCs@MoS / PVDF fabric was subjected to high voltage polarization under the following conditions: polarization temperature 100 °C, polarization voltage 15 kV, and polarization time 4 h. 2 / PVDF composite piezoelectric material.
[0115] Example 10
[0116] The present application embodiment provides α6-CNCs@MoS 2 / The preparation method of PVDF piezoelectric nanogenerator specifically comprises:
[0117] The obtained α6-CNCs@MoS 2 / PVDF composite piezoelectric material, set on α6-CNCs@MoS 2The conductive layer iron on the upper and lower surfaces of the / PVDF composite piezoelectric material, the encapsulation layer polytetrafluoroethylene film respectively covered on the conductive layer, and the wires respectively connected to the conductive layer are composited to obtain α6-CNCs@MoS 2 / PVDF piezoelectric nanogenerator.
[0118] At the same time, in order to verify the CNCs@MoS prepared in the above examples 2 / PVDF piezoelectric nanogenerator's comprehensive performance, this application provides the following comparative examples for detailed description.
[0119] Comparative Example 1
[0120] This comparative example provides a method for preparing a β1-PVDF piezoelectric nanogenerator, which specifically includes:
[0121] S701: weigh 30 g of PVDF and add it into 70 g of DMF, and mechanically stir it at 70° C. for 2 h to obtain a PVDF solution with a mass fraction of 30%;
[0122] S702: The obtained PVDF solution is degassed at a pressure of 0.7 MPa, and then the solution is wet-spun according to the process of coagulation bath, primary drawing bath (drawing temperature 80°C, drawing ratio 3), secondary drawing bath (drawing temperature 80°C, drawing ratio 2), washing bath (temperature 25°C), heat drying (temperature 100°C), and winding to obtain β1-spun fibers. The specification of the spinneret is 50 holes × 0.2 mm, and the spinning pressure is 0.3 MPa;
[0123] S703: The obtained β1-spun fiber is subjected to post-stretching (stretching ratio is 2) through a process of heat stretching and heat setting to obtain β1-PVDF fiber; wherein the heat stretching temperature is 80° C. and the heat setting temperature is 100° C.
[0124] S704: twisting the obtained β1-PVDF fiber and weaving it into a fabric by a weaving method, and subjecting the PVDF fabric to high voltage polarization, the polarization conditions are: polarization temperature of 100° C., polarization voltage of 15 kV, and polarization time of 4 h, to obtain a β1-PVDF piezoelectric material;
[0125] S705: Compounding the obtained β1-PVDF piezoelectric material, the conductive layer iron disposed on the upper surface and the lower surface of the β1-PVDF piezoelectric material, the encapsulation layer polytetrafluoroethylene film respectively covering the conductive layer, and the wires respectively connected to the conductive layer to obtain a β1-PVDF piezoelectric nanogenerator.
[0126] Comparative Example 2
[0127] This comparative example provides a method for preparing β2-CNCs@MoS 2 / The preparation method of PVDF piezoelectric nanogenerator specifically comprises:
[0128] S801: Weigh 1.5 g of dried CNCs and 1.5 g of MoS 2 After grinding and mixing, the powder was added to 100 g of deionized water and stirred at room temperature to mix the powder evenly in the water. The powder was then ultrasonically treated. The upper suspension after centrifugation was transferred to an evaporating dish and freeze-dried to obtain CNCs@MoS 2 Composite materials;
[0129] S802: Weigh 2 g CNCs@MoS 2 The composite material and 30.6 g PVDF were added into 70 g DMF and mechanically stirred at 70 °C for 2 h to obtain β2-CNCs@MoS with a mass fraction of 31%. 2 / PVDF composite solution;
[0130] S803: The obtained β2-CNCs@MoS 2 The / PVDF composite solution was degassed under a pressure of 0.7MPa, and then the solution was wet-spun according to the process of coagulation bath, primary drawing bath (drawing temperature 60℃, drawing ratio 2), secondary drawing bath (drawing temperature 60℃, drawing ratio 2), washing bath (temperature 20℃), heat drying (temperature 120℃), and winding to obtain β2-spun fibers. The specifications of the spinneret are 50 holes × 0.2mm, and the spinning pressure is 0.3MPa;
[0131] S804: The obtained β2-CNCs@MoS 2 / PVDF fibers were twisted and woven into β2-CNCs@MoS 2 / PVDF fabric and β2-CNCs@MoS 2 The β2-CNCs@MoS / PVDF fabric was obtained by high voltage polarization under the following conditions: polarization temperature 80℃, polarization voltage 10kV, and polarization time 2h. 2 / PVDF composite piezoelectric material;
[0132] S805: The obtained β2-CNCs@MoS 2 / PVDF composite piezoelectric material, set on β2-CNCs@MoS 2 The β2-CNCs@MoS / PVDF composite piezoelectric material is composited with conductive layer copper on the upper and lower surfaces, encapsulation layer polyimide films respectively covering the conductive layers, and wires respectively connected to the conductive layers to obtain the β2-CNCs@MoS 2 / PVDF piezoelectric nanogenerator.
[0133] Comparative Example 3
[0134] This comparative example provides a method for preparing β3-MoS 2 / The preparation method of PVDF piezoelectric nanogenerator specifically comprises:
[0135] S901: Weigh 2.5 g of dried MoS 2 The powder was ground and then added to 100 g of deionized water. The powder was stirred at room temperature to make it uniformly mixed in the water. The powder was then ultrasonically treated and freeze-dried to obtain MoS 2 Material;
[0136] S902: weigh 2g MoS 2 The material and 30.6 g PVDF were added into 70 g DMF and mechanically stirred at 70 °C for 2 h to obtain β3-MoS with a mass fraction of 31%. 2 / PVDF composite solution;
[0137] S903: The obtained β3-MoS 2 The / PVDF composite solution was degassed under a pressure of 0.7MPa, and then the solution was wet-spun according to the process of coagulation bath, primary drawing bath (drawing temperature 60℃, drawing ratio 2), secondary drawing bath (drawing temperature 60℃, drawing ratio 2), washing bath (temperature 20℃), heat drying (temperature 120℃), and winding to obtain β3-spun fibers. The specifications of the spinneret are 50 holes × 0.2mm, and the spinning pressure is 0.3MPa;
[0138] S904: The obtained β3-spun fiber is subjected to post-stretching (stretching ratio is 6) through the process of heat stretching and heat setting process to obtain β3-MoS 2 / PVDF fiber; wherein the heat drawing temperature is 80°C and the heat setting temperature is 100°C;
[0139] S905: The obtained β3-MoS 2 The / PVDF fibers were twisted and woven into fabrics, and the β3-MoS 2 The β3-MoS / PVDF fabric was obtained by high voltage polarization under the following conditions: polarization temperature 80℃, polarization voltage 10kV, and polarization time 2h. 2 / PVDF composite piezoelectric material;
[0140] S906: The obtained β3-MoS 2 / PVDF composite piezoelectric material, set in β3-MoS 2 The conductive layer copper on the upper surface and the lower surface of the / PVDF piezoelectric material, the encapsulation layer polyimide respectively covered on the conductive layer and the wires respectively connected to the conductive layer are compounded to obtain the β3-MoS2 / PVDF piezoelectric nanogenerator.
[0141] In order to verify the CNCs@MoS prepared in this embodiment 2 The structural properties of the composite materials are shown in Figure 2. 2 The composite material was characterized and the results were Figure 3 As shown. Among them, Figure 3 For the preparation of CNCs, MoS 2 and CNCs@MoS 2 X-ray diffraction pattern of .
[0142] according to Figure 3 It can be seen that MoS 2 It shows a series of strong diffraction peaks corresponding to 2H phase MoS 2 , MoS after CNCs peeling 2 , the (002) diffraction peak becomes broader and weaker, and other diffraction peaks disappear, indicating that the exfoliated MoS 2 The less stacking indicates that MoS2 is successfully exfoliated into single-layer or few-layer nanosheets.
[0143] In order to verify the CNCs@MoS prepared in this embodiment 2 The comprehensive performance of the CNCs@MoS / PVDF piezoelectric nanogenerator prepared in Example 2 / PVDF piezoelectric nanogenerator was characterized and the results were Figures 4 to 9 As shown. Among them, Figure 4 The prepared α1-spun fibers, β1-PVDF fibers and α1-CNCs@MoS 2 / Stress-strain curve of PVDF fiber; Figure 5 α1-CNCs@MoS 2 Variable temperature infrared spectra of / PVDF fiber and β1-PVDF fiber; Figure 6 α1-spun fibers, β1-PVDF fibers and α1-CNCs@MoS 2 / X-ray diffraction pattern of PVDF fiber; Figure 7 α1-CNCs@MoS 2 Piezoelectric constant diagram of / PVDF composite piezoelectric material and β1-PVDF piezoelectric material; Figure 8 β1-PVDF piezoelectric nanogenerator, β3-MoS 2 / PVDF piezoelectric nanogenerator and α1-CNCs@MoS 2 / The voltage generated by the PVDF piezoelectric nanogenerator under a periodic pressure of 10 kPa; Fig. 9 ɑ1-CNCs@MoS 2 / Image of PVDF piezoelectric nanogenerator monitoring human movement.
[0144] according to Figure 4 It can be seen that after post-stretching, the tensile strength of β1-PVDF fiber increased from the original 97.3MPa to 222.3MPa. 2 The tensile strength of / PVDF fiber is 304.4MPa, indicating that the material has excellent mechanical properties.
[0145] according to Figure 5 It can be seen that, among them, a) Figure α1-CNCs@MoS 2 / PVDF fiber, 3450cm -1 The absorption band at 840cm is attributed to the hydrogen bonding between PVDF and CNCs. As the temperature increases, the intensity of the hydrogen bonding absorption band gradually decreases. Due to the sensitivity of hydrogen bonding to temperature, the spectral changes correspond to the breaking of hydrogen bonds. In order to exclude the influence of hydrogen bonding between PVDF molecules. As shown in Figure b), it can be seen that the intensity of the hydrogen bonding absorption band in β1-PVDF fiber is significantly lower than that observed in the composite fiber. As shown in Figure c), when the temperature is below 180°C, at 840cm -1 and 1276cm -1 α1-CNCs@MoS 2 As shown in Figure d), the intensity of the corresponding absorption band of the electroactive β phase in β1-PVDF fiber is significantly lower than that in α1-CNCs@MoS 2 These phenomena are attributed to the ion-dipole interaction and hydrogen bonding interaction between CNCs and PVDF.
[0146] according to Figure 6 It can be seen that α1-CNCs@MoS 2 Compared with α1-nascent fibers and β1-PVDF fibers, the content of electrically active β phase in the / PVDF fibers gradually increased after post-treatment with hot stretching-heat setting process, indicating that the hot stretching-heat setting process is crucial to the improvement of electrical properties.
[0147] according to Figure 7 It can be seen that α1-CNCs@MoS 2 Compared with the β1-PVDF piezoelectric material and the PVDF composite piezoelectric material, it shows that CNCs@MoS 2 The addition of materials, through the synergistic effect of the two, can improve the piezoelectric constant of the piezoelectric material.
[0148] according to Figure 8 It can be seen that β1-PVDF piezoelectric nanogenerator, β3-MoS2 / PVDF piezoelectric nanogenerator and α1-CNCs@MoS 2 Voltage diagram of the α1-CNCs@MoS / PVDF piezoelectric nanogenerator under 5 kPa periodic pressure. 2 / PVDF piezoelectric nanogenerator has the largest voltage, which indicates that CNCs can effectively peel off MoS 2 , thereby activating MoS 2 On the other hand, CNCs can interact with PVDF to promote the formation of electroactive β phase, thereby significantly improving the piezoelectric properties of the composite fibers.
[0149] according to Fig. 9 It can be seen that the prepared ɑ1-CNCs@MoS 2 / PVDF piezoelectric nanogenerator a) is at the finger; b) is at the wrist. The monitoring diagram of human body movement. It can be seen from the figure that with the increase of bending degree, the piezoelectric output increases accordingly, indicating a good monitoring ability of human body movement.
[0150] Table 1 Piezoelectric performance test of embodiments and comparative examples
[0151] Serial number Material Piezoelectric constant / pC / N <![CDATA[Power density / μW / cm 2 > 1 <![CDATA[α1-CNCs@MoS 2 / PVDF composite piezoelectric material]]> 34.5 48.5 2 <![CDATA[α2-CNCs@MoS 2 / PVDF composite piezoelectric material]]> 36.7 51.6 3 <![CDATA[α3-CNCs@MoS 2 / PVDF composite piezoelectric material]]> 38.2 54.3 4 <![CDATA[α4-CNCs@MoS 2 / PVDF composite piezoelectric material]]> 39.4 56.4 5 <![CDATA[α5-CNCs@MoS 2 / PVDF composite piezoelectric material]]> 41.3 58.8 6 <![CDATA[α6-CNCs@MoS 2 / PVDF composite piezoelectric material]]> 42.0 60.6 7 β1-PVDF piezoelectric material 24.5 36.7 8 <![CDATA[β2-CNCs@MoS 2 / PVDF composite piezoelectric material]]> 4.1 9.3 9 <![CDATA[β3-MoS 2 / PVDF composite piezoelectric material]]> 28.5 40.5
[0152] The difference between Comparative Example 1 and Example 1 of the present application is that CNCs@MoS 2 Composite material, according to Table 1, the prepared PVDF piezoelectric nanogenerator has poor piezoelectric performance; the difference between Comparative Example 2 of the present application and Example 1 is that the heat drawing and heat setting process in the post-treatment are not performed, and the prepared β2-CNCs@MoS 2 / PVDF piezoelectric nanogenerator has poor piezoelectric performance; the difference between comparative example 3 of the present application and example 1 is that CNCs are not added, so that the prepared β3-MoS 2 / PVDF piezoelectric nanogenerators have poor mechanical and piezoelectric properties.
[0153] Therefore, the CNCs@MoS 2 MoS / PVDF composite piezoelectric material was first peeled off by CNCs 2 , and obtain CNCs@MoS 2 Materials, and then the prepared CNCs@MoS 2 The CNCs@MoS / PVDF solution was prepared by a wet spinning process of coagulation bath, primary drawing bath, secondary drawing bath, washing bath, heat drying, winding, and subsequent hot drawing, heat setting post-drawing process, twisting, weaving, and high-voltage polarization. By strictly controlling the experimental conditions and process parameters, the prepared CNCs@MoS 2 / PVDF composite piezoelectric materials have excellent piezoelectric and mechanical properties, which endows CNCs@MoS 2 / PVDF piezoelectric nanogenerator has the advantages of excellent mechanical properties, excellent piezoelectric properties and stability.
[0154] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0155] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A method for preparing a CNCs@MoS2 / PVDF composite piezoelectric material, characterized in that: The method comprises: The cellulose nanocrystals were mixed with molybdenum disulfide to prepare CNCs@MoS2 composite materials; Dissolving the CNCs@MoS2 composite material and PVDF in an organic solvent to obtain a CNCs@MoS2 / PVDF composite solution; The CNCs@MoS2 / PVDF composite solution is wet-spinned to prepare primary fibers, and the primary fibers are sequentially subjected to heat drawing and heat setting to obtain CNCs@MoS2 / PVDF fibers; The CNCs@MoS2 / PVDF fiber is twisted, woven and high-voltage polarized in sequence to obtain the CNCs@MoS2 / PVDF composite piezoelectric material.
2. The method for preparing the CNCs@MoS2 / PVDF composite piezoelectric material according to claim 1, characterized in that: The mass ratio of the cellulose nanocrystals to molybdenum disulfide is 1:(1-3).
3. The method for preparing the CNCs@MoS2 / PVDF composite piezoelectric material according to claim 1, characterized in that: The molecular weight of the PVDF is 400,000-700,000; And / or, the mass percentage of the PVDF in the composite solution is 30%-40%; And / or, the organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
4. The method for preparing the CNCs@MoS2 / PVDF composite piezoelectric material according to claim 1, characterized in that: The preparation of the nascent fiber by wet spinning comprises sequentially performing a coagulation bath, a primary drawing bath, a secondary drawing bath, a washing bath, heat drying and winding; And / or, the coagulation bath is a 5%-40% aqueous solution of N,N-dimethylformamide at a temperature of 30-70°C; and / or, the primary drawing bath and the secondary drawing bath are both aqueous solutions at a temperature of 60-90° C.; And / or, the draft ratio of the primary drafting bath is 1-4; and / or, the draft ratio of the secondary drafting bath is 1-3; and / or, the washing bath is a methanol solution at a temperature of 20-30°C; And / or, the thermal drying temperature is 100-150°C.
5. The method for preparing the CNCs@MoS2 / PVDF composite piezoelectric material according to claim 1, characterized in that: When the spun fiber is subjected to heat drawing and heat setting in sequence, the heat drawing temperature is 80-140° C. and the drawing ratio is 2-5; And / or, the heat setting temperature is 100-150°C.
6. The method for preparing the CNCs@MoS2 / PVDF composite piezoelectric material according to claim 1, characterized in that: The high voltage polarization includes corona polarization; The corona polarization temperature is 80-120° C., the voltage is 10-20 kV, and the time is 2-4 hours.
7. A CNCs@MoS2 / PVDF piezoelectric nanogenerator, comprising a piezoelectric material layer, a conductive layer, a packaging layer and a wire, characterized in that: The raw material for preparing the piezoelectric material layer includes the CNCs@MoS2 / PVDF composite piezoelectric material prepared by any preparation method described in claims 1-6.
8. A method for preparing the CNCs@MoS2 / PVDF piezoelectric nanogenerator according to claim 7, characterized in that: The method comprises: After the CNCs@MoS2 / PVDF composite piezoelectric material is prepared into a piezoelectric material layer, a conductive layer and a packaging layer are sequentially arranged on the upper surface of the piezoelectric material layer, and a conductive layer and a packaging layer are sequentially arranged on the lower surface of the piezoelectric material layer, and a wire is used to electrically connect the two conductive layers to obtain the CNCs@MoS2 / PVDF piezoelectric nanogenerator.
9. The method for preparing the CNCs@MoS2 / PVDF piezoelectric nanogenerator according to claim 8, characterized in that: The conductive layer comprises one or more of aluminum, gold, titanium, titanium nitride, titanium silicide, titanium tungsten alloy, tungsten, tungsten silicide, tungsten nitride, nickel, nickel silicide, nickel nitride, tantalum, tantalum nitride, iron, platinum, copper, silver and chromium; And / or, the encapsulation layer includes one or more of a polyimide film, a polyethylene film, a polytetrafluoroethylene film, a polypropylene film, a polystyrene film, and a benzocyclobutene film.
10. Application of a CNCs@MoS2 / PVDF piezoelectric nanogenerator prepared by the preparation method according to any one of claims 8 to 9 in human motion monitoring and energy collection.